Modes of transmission of Glugea plecoglossi (Microspora) via the skin and digestive tract in an experimental infection model using rainbow trout, Oncorhynchus mykiss (Walbaum) - Lee, S-J (Journal of fish diseases, 2004)
Glugea plecoglossi (Microspora) is a significant cause of economic loss in cultured ayu, Plecoglossus altivelis, in Japan, due to the unsightly appearance of infected fish harbouring xenomas in the body cavity. Modes of transmission of G. plecoglossi via the skin and digestive tract were studied in an experimental infection model using rainbow trout, Oncorhynchus mykiss. Combined with Uvitex 2B and in situ hybridization (ISH) assays, the early development of G. plecoglossi was successfully traced. Following a bath exposure of fish Uvitex 2B-labelled G. plecoglossi spores were observed to attach to microscopic injuries (trypan blue-positive sites) of fish skin, after which ISH-positive sporoplasms were found to invade the epidermis as early as 5 min post-infection (PI), migrating rapidly to the subdermis. It was also shown that G. plecoglossi entering via the skin does not spread into the internal organs but develops into subdermal xenomas. After rainbow trout were exposed to G. plecoglossi spores by oral intubation, spores germinated in the intestinal lumen, followed by penetration of sporoplasms into the gut mucosal epithelium 5 min PI. In vitro trials determining stimulation factors (fish mucus, changes in pH, digestive enzymes) for the extrusion of the polar tube were inconclusive. The present study indicates that skin wounds and the gut epithelium can be portals of entry of G. plecoglossi and that natural infection in fish seems to occur perorally rather than via the skin